The Effectiveness of a Combination of Swallowing Exercises with Benson Relaxation and Aromatherapy on the Swallowing Ability of Stroke Patients - Cahyati, Yanti; Ipa, Mara; Rosdiana, Ida (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2024)
Stroke patients with dysphagia require proper initial screening so as not to cause severe complications. More optimal efforts are needed to improve swallowing ability to avoid complications. Swallowing exercises combined with Benson Relaxation and Aromatherapy are expected to provide better results in increasing the swallowing ability score of stroke patients with dysphagia. This study aims to determine the effect of the combination of Swallowing Exercise with Benson Relaxation and Aromatherapy on the swallowing ability of stroke patients. This type of research is a quasi-experimental pre and post-test. Researchers intervened in two groups of respondents. One group intervened with a combination of swallowing exercises with Benson relaxation, and one group combined swallowing exercises with aromatherapy. The sampling technique was consecutive sampling. The number of samples was 44 people: 20 people in Intervention Group I and 25 in Intervention Group II. Statistical analysis used a dependent t-test (paired t-test) to test the difference in the average score of swallowing ability before and after the intervention and an independent t-test to test the difference in the average score after the intervention in intervention groups I and II. This research showed a significant difference in the average score of swallowing ability before and after the intervention in the intervention group I and II, and there is no difference in the average score of swallowing ability after the intervention in the intervention group I and II. Swallowing exercise combined with Benson relaxation and aromatherapy can improve the swallowing ability score of dysphagia patients due to stroke.